Evaluation framework for automatic singing transcription - Molina, Emilio; Barbancho-Pérez, Ana María; Tardón-García, Lorenzo José; Barbancho-Pérez, Isabel (My University, 2014)
In this paper, we analyse the evaluation strategies used in previous works on automatic singing transcription, and we present a novel, comprehensive and freely available evaluation framework for automatic singing transcription. This framework consists of a cross-annotated dataset and a set of extended evaluation measures, which are integrated in a Matlab toolbox. The presented evaluation measures are based on standard MIREX note-tracking measures, but they provide extra information about the type of errors made by the singing transcriber. Finally, a practical case of use is presented, in which the evaluation framework has been used to perform a comparison in detail of several state-of-the-art singing transcribers.
Keywords: Música - Proceso de datos; MIR; Music Information Retrieval; Singing transcription; Transcription evaluation; Audio signal processing